(untitled) (Indian Journal of Public Health Research & Development, 2023)
Abstract Background: In 2021 only very few COVID-19 vaccines were anticipated in India. There is lag in vaccination drive & scanty literature on perception of front-line workers on COVID-19 vaccination. The study was planned to get an insight into vaccination effects, side effects & acceptance. Methods: A cross-sectional study was conducted among front-line workers in a tertiary healthcare institute from March - May 2021 through an online google survey form. The data of the study was collected & analysed using percentage. Results: 84% were 21 to 30 years of age, 51% were male. Almost 90.4% had taken 2 doses of vaccination, majority had Covaxin (91.5%). 10.6% & 26.5% delayed taking 1st jab & 2nd jab, attributed to fear of side effects, unavailability, tested positive for covid-19. Around 61.7% experienced side effects & majority had myalgia, injection site pain. Most of them perceived it effective in terms of less severity of disease after vaccination. Other prophylactic measures included (95.7%) covid precautions, (40.4%) Ivermectin, (25.5%) immune boosters & (18%) home remedies, 75.5% perceived vaccination as best way to tackle pandemic, whereas 23% stated natural immunity is better. 68% vouched for given opportunity to choose their vaccine, 47.9% preferred government setup. Conclusion: All perceived it effective with minimal side effects. Although initially doubtful later showed full acceptance towards vaccines. Based on evidence study recommends administrative strengthening, provision of opportunity to choose vaccines, capacity building of vaccinators & vaccine awareness.